The Border of Responsibilities in Global Distribution of Aid: Ethical Issues and Challenges in Practices - Pertiwi, Mutiara (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2018)
This essay intends to analyse the debate about responsibility in the discourse of global justice. The topic is inspired by the statement of Thomas Pogge who argues that the minor outcome in promoting global justice is generated by a deep ethical problem on the question of responsibility rather than a technical problem such as taxation and liberalisation policy (2001a). He argues that many global problems would be solved if only the affluent countries perceived their roles in sending foreign aid as a responsibility and not as charity, which is how many communitarians perceive it. This ethical debate will be the concern of my essay. The main agenda is to find the most convincing argument for ethical guidance in the current world. Analysing through the lense of Bertrand Russell's (1961) parameter of ‘commendable ethics,' this essay validates Pogge's position that foreign aid from affluent states is part of negative responsibility and therefore commendable as an ethical guide in promoting global justice.